PENGARUH KOMPETENSI KEPRIBADIAN DAN EFIKASI DIRI GURU TERHADAP KINERJA GURU YANG DIMEDIASI OLEH KOMITMEN ORGANISASIONAL STUDI PADA GURU SMK NEGERI SWASTA SERAYON BATANG BARAT KABUPATEN BATANG - Riyanto, 12 5202 0254; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze the influence of personal competence, self-efficacy of teachers and teachers organizational commitment to performance and the role of organizational commitment mediates the influence of personal competence and teachers self efficacy on performance of teachers on vocational high school teachers of west Batangâs Rayon on Batang Regency. The populationÂ  in this research is state and private vocational high school teachers of west Batangâs rayon on Batang Regency, totaledÂ  211 people. With Slovin method then the sample numberedÂ  138 people. Then from 138 people, who returns the answer of the questionnaire amounted to 136 people. The results showed that (1) personal competence and a significant positive effect on organizational commitment, (2) self-efficacy of teachers is also positive and significant effect on organizational commitment, (3) personal competence and a significant positive impact on teacher performance, (4) self-efficacy teacher positive and significant impact on teacher performance, (5) personal competence and a significant positive effect on teacher performance, (6) organizational commitment does not mediate the influence of personal competence on teachers performance, (7) organizational commitment does not mediate the influence of self-efficacy of teachers on teacher performance . Keywords: personal competence, self-efficacy of teachers, teachers